Fabrication and evaluation of molecularly imprinted magnetic nanoparticles for selective recognition and magnetic separation of lysozyme in human urine. Issue 23 (1st November 2018) - Zhang, Zulei; Wang, Hongmei; Wang, Hailong; Wu, Cuichen; Li, Mengli; Li, Lei
Abstract : The Lyz-MMIPs displayed a uniform core–shell structure, favorable magnetic properties, good accessibility, and good stability and had a good affinity and excellent binding selectivity to Lyz. Abstract : In this study, lysozyme-based magnetic molecularly imprinted polymers (Lyz-MMIPs) for selective recognition and magnetic separation of lysozyme in human urine were prepared via surface imprinting technology. The morphology and structural properties of the resultant Lyz-MMIPs were characterized by using transmission electron microscopy (TEM), Fourier transform infrared (FT-IR) spectroscopy, X-ray photoelectron spectroscopy (XPS), thermogravimetry (TG), X-ray diffraction (XRD) and a vibrating sample magnetometer (VSM). The results showed that the Lyz-MMIPs exhibited a uniform core–shell structure and favorable magnetic properties with a saturation magnetization of 14.8 emu g −1 . To obtain the best selectivity and binding performance, the pH value of adsorption solution was investigated in detail. Under the optimized conditions, the Lyz-MMIPs possessed high binding and specific recognition capacity, as well as fast binding kinetics and phase separation rates. Moreover, the saturation binding capacity of Lyz-MMIPs reached 124.3 mg g −1, which was nearly 3.2 times that of lysozyme-based magnetic non-imprinted polymers (Lyz-MNIPs). In addition, the selectivity and reusability experiments showed that the Lyz-MMIPs displayed significant selectivity and favorable reusability. Furthermore, the Lyz-MMIPs were successfully applied for the determination and separation of lysozyme in human urine with satisfactory recovery rates. Above all, the synthetic process was quite simple and this strategy may provide a versatile approach for the fabrication of well-defined molecularly imprinted polymers on magnetic nanoparticles for the analysis of complicated matrixes.